KAJIAN YURIDIS TERHADAP PUTUSAN BEBAS BAGI PELAKU TINDAK PIDANA KORUPSI DI PENGADILAN TIPIKOR SEMARANG - Purwoto, Fransisca Putri Pertiwi, Nyoman Serikat *), (Diponegoro Law Journal, 2013)
The growth of corruption that has been increasing year by year and the difficulty of eradicating corruption will bring disaster not only to the national economic life but also the lives of the state and nation at large. Therefore, corruption cannot be classified as an ordinary crime but has become an extraordinary crime that corruption needs to be taken seriously.This type of research in writing this law using normative research, sources of data in this study is a secondary data source. Data collection methods used in the writing of this law is the study of literature, while the data analysis method used is descriptive qualitative. In practice, commonly called acquittal verdict, which means the defendant legally and convincingly not guilty to charges of corruption or also be mentioned that the defendant can not be convicted criminal.Legally it can be concluded that the acquittal may be taken by the judges if after checking case and deliberation will assume that : a.) The lack of evidence as proof of a minimum prescribed by law negatively (negatief wettelijke bewijs theorie) as adopted by the KUHAP. ; b.) The judges argue against the principle of the minimum evidence established by statute have been met,Â  for example in the form of the two witnesses or clue, judges are not convinced of the defendant's guilt. Then the defendant should be acquitted.Â